The Nature of the State of Nature: Hobbes, Sovereignty and Biopolitics - Popp-Madsen, Benjamin Ask (Politik, 2014)
The large amount of theoretical debates over the notion of biopolitics originally emerges from Michel Fou- cault’s discussions of sovereignty, disciplinary power and biopolitics. Here, biopolitics is conceptualised as a qualitatively di erent and modern regime of power developed in contrast to the model of sovereignty. e ultimate theorist of sovereignty in the canon of Western political thought is omas Hobbes, and in Leviathan two important transitions for the sovereign model takes place: the human being transcends his animal-like condition and becomes a subject, a transition from the image of homo homini lupus to the image of the political subject, and the relation between human beings changes from the of war of all against all to the politics of the state, thus the possibility of politics emerges. Interestingly, as the concept of biopolitics is developed against the backdrop of this theory of sovereignty, both Michel Foucault and Giorgio Agamben delivers detailed interpretations of Hobbes’ state of nature. By analysing these interpretations, the article tries to understand the emergence of a distinctively biopolitical conception of man and the political in contrast to the conceptions in the paradigm of sovereignty.